2022
DOI: 10.1037/tra0001202
|View full text |Cite
|
Sign up to set email alerts
|

Doomscrolling during COVID-19: The negative association between daily social and traditional media consumption and mental health symptoms during the COVID-19 pandemic.

Abstract: Objective: Consumption of traditional and social media markedly increased at the start of the COVID-19 pandemic as new information about the virus and safety guidelines evolved. Much of the information concerned restrictions on daily living activities and the risk posed by the virus. The term "doomscrolling" was used to describe the phenomenon of elevated negative affect after viewing pandemic-related media. The magnitude and duration of this effect, however, is unclear.Furthermore, the effect of doomscrolling… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 32 publications
3
40
0
Order By: Relevance
“…Though a negative association between Internet usage and PTSD symptoms was observed in this analysis, this finding was just below the threshold for statistical significance. While certain aspects of Internet usage, such as consumption of pandemic-related media (“doomscrolling”) have been associated with PTSD (Price et al, 2022 ), the Internet may also be used for social connection, communication of vital information, purchase of essentials and even healthcare (“telemedicine”) during periods of confinement or isolation (Farsi et al, 2022 ). The role of the Internet in shaping positive or negative psychological responses to COVID-19 is complex, and requires further elucidation along multiple vectors in diverse populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though a negative association between Internet usage and PTSD symptoms was observed in this analysis, this finding was just below the threshold for statistical significance. While certain aspects of Internet usage, such as consumption of pandemic-related media (“doomscrolling”) have been associated with PTSD (Price et al, 2022 ), the Internet may also be used for social connection, communication of vital information, purchase of essentials and even healthcare (“telemedicine”) during periods of confinement or isolation (Farsi et al, 2022 ). The role of the Internet in shaping positive or negative psychological responses to COVID-19 is complex, and requires further elucidation along multiple vectors in diverse populations.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence of a link between higher social media usage and PTSD symptomatology. This may be due to the “sensitizing” effect of repeated exposure to pandemic-related images and stories on vulnerable individuals exposed to pandemic-related traumatic stressors (Ikizer et al, 2021 ; Price et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike previous pandemics, the intense use of social media today has caused the news of illness and death, the photos and videos of diseased persons, to be constantly present in lives of individuals. All of these factors have a great potential to provoke additional anxiety and depression [26].…”
Section: Discussionmentioning
confidence: 99%
“…Management of cancer patients with COVID-19 is difficult during the outbreak. Stress, anxiety and depression worsen the clinical outcomes of cancer [24][25][26][27]. In the management of cancer patients, psychological evaluation is quite important, and there is a need for emergency screening and intervention programs.…”
Section: Discussionmentioning
confidence: 99%
“…The Crisis Text Line service reported receiving a higher-than-average volume of messages every day since March 16, 2020, with the main topics being anxiety, depression, grief, and eating disorders [ 7 ]. Price et al [ 8 ] also found that daily doomscrolling —repeatedly consuming negative news and media content on the web—was associated with same-day increases in depression and posttraumatic stress disorder. The pandemic also influenced the type of content that people discussed on social media, with users shifting away from “self-focused” perspectives and toward more “other-focused” topics that used to be taboo to discuss [ 9 ].…”
Section: Introductionmentioning
confidence: 99%